Slogans et stratégies humoristiques des manifestants algériens lors du mouvement populaire - Souad Benabbes (Multilinguales)
During crises of the legitimacy of institutions, demonstrations become not only a moment of uprising, but also of creativity that is expressed with humor and glee. This contribution addresses the issue of political humor that stained the slogans brandished by Algerian demonstrators during the popular movement in public places. We will propose to analyze the various humorous facts in order to answer the following questions : what types of humor are used by Algerian protesters to claim their rights and express their dissatisfaction with the symbols of the regime ? In what language, their humorous speech was obviously more impactful ?